Unity and Diversity in the Gospels and Paul : Essays in Honor of Frank J. Matera - Skinner, Christopher W.; Iverson, Kelly R.; Matera, Frank J. (Early Christianity and its literature, 2012)
"This volume addresses the perennial issue of unity and diversity in the New Testament canon. Celebrating the academic legacy of Fr. Frank J. Matera, colleagues and friends interact with elements of his many important works. Scholars and students alike will find fresh and stimulating discussions that navigate the turbulent waters between the Gospels and Paul, ranging from questions of Matthew's so-called anti-Pauline polemic to cruciform teaching in the New Testament."--Publisher's description.